2008
DOI: 10.1143/jjap.47.661
|View full text |Cite
|
Sign up to set email alerts
|

Change in Electrical Resistivity of NiFe2O4 Porous Bulks Caused by Adsorption and Desorption of Alcohols

Abstract: We present preliminary results on the resummation of leading and next-to-leading logarithms for the thrust distribution in deep inelastic scattering. Our predictions, expanded to O(α 2 s ), are compared with corresponding results from the Monte Carlo programs DISASTER++ and DISENT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The electrical resistivity of porous sintered bodies and thin film of NiFe 2 O 4 nanoparticles is changed by the adsorption and desorption of chlorine, 4) petroleum, 5) alcohol, 6) and other molecules. 7) This property implies that not only charge carriers, which influence the resistivity, but also spin directions, which influence the magnetization, can be controlled by organic matter adsorption and desorption. As mentioned above, it was indeed reported that magnetic properties were changed by organic matter adsorption and desorption.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical resistivity of porous sintered bodies and thin film of NiFe 2 O 4 nanoparticles is changed by the adsorption and desorption of chlorine, 4) petroleum, 5) alcohol, 6) and other molecules. 7) This property implies that not only charge carriers, which influence the resistivity, but also spin directions, which influence the magnetization, can be controlled by organic matter adsorption and desorption. As mentioned above, it was indeed reported that magnetic properties were changed by organic matter adsorption and desorption.…”
Section: Introductionmentioning
confidence: 99%
“…NiFe 2 O 4 nanoparticles in contact with organic compounds display a variety of unique properties. The electrical resistivity of such nanoparticles, either as porous sintered bulk specimens or as thin films, has been shown to vary following the adsorption and desorption of chlorine [2], petroleum [3], alcohols [4], and other substances [5]. This behavior has been explained as the result of charge carrier density changes caused by field effects upon adsorption and desorption of these molecules.…”
Section: Introductionmentioning
confidence: 99%